Transcriptomic Analysis Reveals New Insights into High-Temperature-Dependent Glume-Unclosing in an Elite Rice Male Sterile Line - Fu, Chongyun; Wang, Feng; Liu, Wuge; Liu, Dilin; Li, Jinhua; Zhu, Manshan; Liao, Yilong; Liu, Zhenrong; Huang, Huijun; Zeng, Xueqin; Ma, Xiaozhi (Frontiers in Plant Science, 2017)
Glume-unclosing after anthesis is a widespread phenomenon in hybrid rice and also a maternal hereditary trait. The character of Glume-unclosing in rice male sterile lines also seriously influences germination rate and the commercial quality of hybrid rice seeds. We validated that the type of glume-unclosing after anthesis in the elite rice thermo-sensitive genic male sterile (TGMS) line RGD-7S was caused by high temperature. Transcriptomic sequencing of rice panicles was performed to explore the change of transcript profiles under four conditions: pre- and post-anthesis under high temperature (HRGD0 and HRGD1), and pre- and post-anthesis under low temperature (LRGD0 and LRGD1). We identified a total of 14,540 differentially expressed genes (DEGs) including some heat shock factors (HSFs) across the four samples. We found that more genes were up-regulated than down-regulated in the sample pair HRGD1vsHRGD0. These up-regulated genes were significantly enriched in the three biological processes of carbohydrate metabolism, response to water and cell wall macromolecular metabolism. Simultaneously, we also found that the HSF gene OsHsfB1 was specially up-regulated in HRGD1vsHRGD0. However, the down-regulated DEGs in LRGD1vsLRGD0 were remarkably clustered in the biological process of carbohydrate metabolism. This suggests that carbohydrate metabolism may play a key role in regulation of glume-unclosing under high temperature in RGD-7S. We also analyzed the expression pattern of genes enriched in carbohydrate metabolism and several HSF genes under different conditions and provide new insights into the cause of rice glume-unclosing.